THE PERAN VIHARA ANANDA AVALOKITESVARA TERHADAP PLURALISME BERAGAMA DI RANGKASBITUNG - Achmad Maftuh Sujana; Raju Rizky Muhammad (Historia, 2027)
Indonesia is one of the largest multicultural countries in the world characterized by high diversity of religions, ethnicities, languages, cultures, and traditions. Therefore, according to Abdurrahman Wahid (Gus Dur) sociology of religion, houses of worship are no longer seen solely as places for religious rituals, but also as social institutions that have educational, cultural, and community functions. Therefore, this study aims to be a model of good practice for other religious institutions in building an inclusive, tolerant, and harmonious community life. This study uses a qualitative method (Field Research) with data collection techniques through observations conducted at the Ananda Avalokitesvara Rangkasbitung Temple, interviews with the temple administrators, and documentation. This study resulted in a discussion that initially in 1934 it was named Sam Kaw Hwee then in 1970 changed its name to the Ananda Avalokitesvara Temple. In addition, the Ananda Avalokitesvara Temple has a role in the pluralism of religious harmony in the form of social services, blood donation, distribution of basic necessities, assistance to the underprivileged, assistance for disaster victims, and participation in the Republic of Indonesia's independence parade by displaying Barongsai art, so that this pluralism includes: (1) Humanist pluralism; (2) Cultural pluralism; (3) Dialogic pluralism; (4) Inclusive pluralism.